2008
DOI: 10.1007/s10517-008-0085-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of dihydroquercetin genotoxicity

Abstract: Genotoxic properties of dihydroquercetin were in vivo studied by the method of chromosome aberrations counting and DNA-comet assay. Dihydroquercetin administered repeatedly (5 times, 0.15 and 1.5 mg/kg) or once in doses of 15, 150, and 2000 mg/kg induced no DNA damages in mouse bone marrow, blood, liver, and rectal cells. Single administration of this preparation in doses of 1.5 and 150 mg/kg and 5-fold administration in a dose of 1.5 mg/kg had no effect on the level of chromosome aberrations in mouse bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…The safety profile of taxifolin has been studied previously [7, 79]. Consistent with these reports, animal survival rates were comparable among vehicle- or taxifolin-treated WT and Tg-SwDI mice groups (Fig.…”
Section: Resultssupporting
confidence: 85%
“…The safety profile of taxifolin has been studied previously [7, 79]. Consistent with these reports, animal survival rates were comparable among vehicle- or taxifolin-treated WT and Tg-SwDI mice groups (Fig.…”
Section: Resultssupporting
confidence: 85%
“…The experimental substance did not affect antibody-forming cells of the spleen or alter the hemagglutinin titer in the serum or result in any delayed-type hypersensitivity or graft versus host reactions. Previous studies reported by Zhanataev et al, 29 that assessed DHQ’s genotoxicity in the chromosome aberration test and the DNA-comet assay, found a lack of evidence of the compound’s genotoxicity. In their studies, DHQ was administered 5 times at 0.15 or 1.5 mg/kg, or in a single dose of 15, 150, or 2000 mg/kg, in 8- to 12-week-old male and female C57B1/6 mice (18-20 g) and found to induce no DNA damage in bone marrow, or blood, liver, and rectal cells.…”
Section: Discussionmentioning
confidence: 92%
“…As genotoxicity [41] and mutagenicity [42] of TXF have been demonstrated to be very low, this phytochemical is considered to be a highly safe hypoglycemic and hypouricemic biofactor.…”
Section: Discussionmentioning
confidence: 99%